IDEOLOGY OF THE STORY CUPAK KE SWARGAN BY PUPPET MASTER I MADE JANGGA: IN THE PERSPECTIVE OF CULTURAL STUDIES - Murtana, I Nyoman; Suastika, I Made; Dibia, I Wayan; Kutha Ratna, I Nyoman (E-Journal of Cultural Studies, 2012)
This dissertation contains the result of the research in the ideology of thestory or Lakon Cupak Ke Swargan (hereon abbreviated to LCS) by the puppetmaster or Dalang Jangga, in a performance of Wayang Cupak at Dukuh PuluTengah, Mambang Village, East Selemadeg District. This story conveys anumber of life values which are expressed ideologically through various events,including a power struggle, a love story, and a search for God. All the events areexpressed aesthetically so that audience can enjoy the performance.The target of the research is a performance of LCS by Dalang Jangga in arecording by Aneka Record Tabanan, which the writer transcribed in the form of awritten text. The research focuses on the idelogy contained in LCS. The type ofdata used was qualitative data about the ideology that was assumed to be found inthis story. The qualitative data associated with the life of the late Dalang Jangga,in relation to his work in the field of shadow puppet theater, was based on the datacollected in the field through in-depth interviews with a number of informants,using a snowball technique. A post-modern approach was applied through phenomenological,deconstructive, and critical paradigms. The analysis was carried outusing an analytical descriptive technique based on an interpretation of the datacollected. The focus of the analysis was directed by applying three theories,namely theories of ideology, function, and semiotics.Three main topics were obtained from the analysis of the data, namely theform, function, and meaning of the ideology. By studying the ideological form, itwas possible to gain a picture about the conservative, progressive, and pragmatic ideology of Dalang Jangga. From the ideological function, the writer gained anidea of its social dynamic, educational, ritual, and aesthetical. A study of theideological meaning provided an illustration of the symbolic, ethical, andaesthetical meanings.
Keywords: ideology, Cupak Ke Swargan, and Dalang I Made Jangga.